High-resolution 3D reflection seismic investigation over a quick-clay landslide scar in southwest Sweden - Lundberg, E.; Malehmir, A.; Juhlin, Christopher; Bastani, M.; Andersson, M. (Society of Exploration Geophysicists, 2014)
Quick-clay landslides often occur in the northern hemisphere in areas that were covered by Pleistocene glaciations. They are particularly common along the shorelines of the Göta River in southwestern Sweden. Characterization of potential landslide areas and identification of features that indicate high risk are necessary to better understand the triggering mechanisms of these events. Therefore, an intensive characterization project was initiated at the Fråstad landslide in Sweden. Part of the characterization program included the acquisition of 3D reflection seismic data to image structures in the normally consolidated sediments, as well as the bedrock topography below the landslide scar. Two seismic horizons within the glacial and postglacial sediments were observed. The shallowest seismic horizon (here, referred to as S1) corresponds to a coarse-grained layer that was previously detected by eight geotechnical boreholes located within the 3D survey area. Discontinuities in S1, mapped by the 3D reflection seismic data, occur across a zone that correlates with the landslide scar boundary, suggesting that this zone may have played a role in triggering and/or in limiting the extension of the landslide. If S1 is truncated by or mixed with clays in this zone, then the outflow of water from the permeable S1 into the clays above may have increased the amount of quick clays above this zone. The increased outflow of water may also have caused a higher pore-water pressure south of the zone, which in turn could have acted as a trigger for the landslide. We evaluated the potential of using the 3D reflection seismic method as a complement to drilling and other geophysical methods when performing landslide site investigations. We also demonstrated the importance of further investigating the relationship between 3D subsurface geometries and landslide development.